2019
DOI: 10.1186/s12882-019-1404-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury and the risk of mortality in patients with methanol intoxication

Abstract: Background Methanol poisoning is a serious public health issue in developing countries, but few data are available in the literature on acute kidney injury (AKI) after methanol intoxication. Methods This study examined the clinical features, spectrum and outcomes of AKI in patients with methanol intoxication and evaluated the predictors of mortality after methanol intoxication. A total of 50 patients with methanol intoxication were seen at Chang Gung Memorial Hospital b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
7
16
2
Order By: Relevance
“…To the best of our knowledge, this is the rst study on the association between comprehensive analysis of electrocardiographic ndings and mortality in methanol toxicity with a considerable sample size. The mortality rate in this study was 16.6% which is comparable with various published data [4,13,14]. Furthermore, the mortality rate was higher among female patients and patients aged above 40 years.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…To the best of our knowledge, this is the rst study on the association between comprehensive analysis of electrocardiographic ndings and mortality in methanol toxicity with a considerable sample size. The mortality rate in this study was 16.6% which is comparable with various published data [4,13,14]. Furthermore, the mortality rate was higher among female patients and patients aged above 40 years.…”
Section: Discussionsupporting
confidence: 90%
“…As expected, patients with a past history of cardiac diseases showed a higher mortality rate. Moreover, the results further highlighted the correlation between the development of complications such as blindness and renal problems and increased morbidity and mortality, which is in line with previous evidences [13,14].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…study on 50 methanol patients showed acute kidney injury in 33 patients (66%) and concluded as a useful predictor of hospital mortality. [18] In a study by Verhelst et al ., acute renal injury was found in 15 of 25 (60%) patients. [19] Salek et al .…”
Section: Discussionmentioning
confidence: 99%
“…Methanol is metabolized to formate (formic acid), which is responsible for visual impairment, blurred vision, impaired visual field and ultimately blindness. Other complications and adverse effects of methanol poisoning include: meta-bolic acidosis, coma, multi-organ failure and even death [2][3][4][5][6]. Because of high prevalence and mortality in Iran due to methanol intoxication, early diagnosis and effective treatment is of clinical significance [7].…”
Section: Introductionmentioning
confidence: 99%